Cellular and molecular mechanisms of multistep carcinogenesis: relevance to carcinogen risk assessment. - Barrett, J C (1987)
Carcinogenesis is a multistep process involving alterations in at least two distinct classes of genes. Protooncogenes are activated qualitatively or quantitatively in certain tumors, and they appear to act as positive proliferative signals for neoplastic growth. In contrast, tumor suppressor genes are normal genes that must be inactivated or lost for tumor development. When active, tumor suppressor genes control neoplastic growth in a negative manner. Chemicals may influence the carcinogenic process by mutational activation of protooncogenes and/or inactivation of tumor suppressor genes. The types of genetic alterations involved in these mutational events are diverse, and their dose-response curves may be varied. In addition, chemical carcinogens may act on nonmutational processes such as the clonal expansion of premalignant cells. The carcinogenic risk of a specific chemical is a composite of its effects on multiple genetic and epigenetic processes.